«НЕЧІТКА АРИФМЕТИКА» як засіб оцінювання економічного ефекту від зміни строків виконання будівельних робіт - Сорокіна, Л. В.; Гойко, А. Ф.; Регіда, О. В. (Ways to Improve Construction Efficiency, 2014)
This article proposes a methodological approach to the evaluation of the economic effect produced by all participants investment and construction process due to changes in the construction period. Through the use of "fuzzy arithmetic" on the basis of the developed approach determined the average rate of change of the duration of the construction and the associated level of risk of the customer and the contractor.